A STUDY ON KNOWLEDGE OF PEOPLE ON ARSENIC RISKS ON HEALTH AT SIX COMMUNES AT VU THU DISTRICT, THAI BINH PROVINCES IN 2017 (Vietnam Journal of Community Medicine, 2021)
Objectives: To describe knowledge of people about arsenic risks on health at six communes of Vu Thu district, Thai Binh provinces in 2017.Methodology: A cross-sectional study was conducted on 1184 people aged≥ 18.Result: The study showed 53% of people had never heard about arsenic in food, 32,6% of those recognized that arsenic went into body through food. The percentage of people who knew about places existing arsenic ranged from 11,6% to 36,5%; rate of people who knew the route of arsenic into the body ranged from 1,7% to 38%; those understanding of affected organs ranged from 3% to 22,5%; those understanding of chronic diseases from 3,3% to 21%; understanding the initial signs of arsenic infection from 4% to 23%; understanding of skin signs from 5,4% to 23%; understanding neurological signs from 4,2% to 18%. There was a low rate of people who can recognize foods at risk of arsenic.Conclusion and recommendation: People’s knowledge on arsenic risks is at low level, so it is necessary to have communication strategies on arsenic risks on health at Vu Thu district, Thai Binh.
Keywords: Asen, health, knowledge, communication.